In-situ measurement of outdoor absorbed dose rates at Itagumodi and Iperindo Gold Mining Sites in Osun State, Nigeria - Emumejaye, Kugbere; Uriri, Solomon Akpore; Olaoye, Morohunfoluwa Adeola Adeola; Mustapha, Amidu Olalekan; Gbadebo, Adewole Micheal (Universitas Sebelas Maret, 2024)
The extraction and usage of natural resources, such as gold, contribute to the variability of ambient radiation levels in the natural environment. The study involved measuring the absorbed dose rate at the Itagunmodi and Iperindo gold mining sites in Osun State, Nigeria, using the BlueGeiger-15 dosimeter. The recorded absorbed dose rate (DR) varied between 0.15 and 0.27 microgray per hour. The annual effective dosage (Deff) was assessed to be between 0.22 and 0.33 millisieverts per year for the Iperindo mine and between 0.18 and 0.27 millisieverts per year for the Itagunmodi mine. The mean values annual effective dose for Iperindo and Itagunmodi were 0.28 ± 0.05 and 0.21 ± 0.03 millisieverts per year, respectively. The study also calculated the excess lifetime cancer risk (ELCR) for the Iperindo and Itagunmodi mines, with average values of 9.68 x 10-4 and 7.16 x 10-4, respectively. These values are above the global average of 2.9 x 10-4, suggesting that individuals and workers in the region may have an increased risk of developing cancer during their lifetime.